PENGARUH PERBEDAAN KONSENTRASI PELARUT TERHADAP KADAR FLAVONOID TOTAL DAUN SEGAR DAN DAUN KERING TANAMAN MATOA (Pometia pinnata J.R. & G.FORS) - Kurnianto, Erwan; Rahman, Ika Ristia; Kartikasari, Dian; Hairunnisa (Jurnal Insan Farmasi Indonesia, 2024)
Matoa (Pometia pinnata J.R. & G.FORS.) is a plant that is spread in several regions in Indonesia. This plant contains secondary metabolites that can dissolve in ethanol solvents such as flavonoids. The right type of solvent is very necessary to obtain maximum levels of active compound. This study examines the effect of ethanol solvent concentration on the total flavonoid content of fresh and dry leaves of the matoa (Pometia pinnata J.R. & G.FORS). Extraction was done using the maceration method with 70%, 80%, and 96% ethanol solvent. The determination of total flavonoid levels was carried out using the UV-Vis spectrophotometric method and AlCl3 as a reagent. The results showed that the total flavonoid content of 70%, 80%, and 96% ethanol extract of fresh matoa leaves were respectively (2.539±0.1047 mgQE/g), (1.885±0.0202 mgQE/g), (1.320±0 .0669 mgQE/g) and dried matoa leaves were (1.110±0.0448 mgQE/g), (0.870±0.0096 mgQE/g), (0.539±0.0130 mgQE/g). Based on statistical tests using the Kruskal-Wallis Test, differences in solvent concentration provide significant differences (p<0.05).